The impact of CYP2D6 polymorphisms on the pharmacokinetics of codeine and its metabolites in Mongolian Chinese subjects - Wu, Xiujun; Yuan, Li; Zuo, Jinliang; Lv, Jing; Guo, Tao (European journal of clinical pharmacology, 2014)
Purpose Codeine is an analgesic drug acting on μ-opioid receptors predominantly via its metabolite morphine formed almost exclusively by CYP2D6 . Genetic polymorphisms in CYP2D6 are associated with diminished pain relief and/or severe opioid side effects. In Chinese individuals, CYP2D6*10 is the most common allele with reduced enzyme activity. In this study, we investigated the effect of this allele on the pharmacokinetics of codeine and its metabolites. Method A blood sample was collected from healthy Mongolian volunteers for CYP2D6 genotyping using a PCR-RFLP assay. A pharmacokinetic study was then carried out in three groups with CYP2D6*1/*1 ( n = 10) , CYP2D6*1/*10 ( n = 10) and CYP2D6*10/*10 ( n = 9) genotypes by collecting serial blood samples for determination of plasma levels of codeine and its metabolites, morphine, morphine 3-glucuronide (M3G) and morphine 6-glucuronide (M6G) before and after a single 30-mg oral dose of codeine phosphate. Codeine and its metabolites were measured by LC-MS/MS. Results No significant differences were observed in the pharmacokinetic parameters of codeine in the three genotype groups. However, the C max and AUC 0-∞ of morphine, M3G and M6G were significantly different between the study groups ( P < 0.05). Compared with the *1/*1 group, the AUC 0-∞ for morphine in the *1/*10 and *10/*10 groups decreased by ratios (95 % CI) of 0.93 (0.26–1.59) and 0.494 (0.135–0.853) respectively. Corresponding ratios for M3G were 0.791 (0.294–1.288) and 0.615 (0.412–0.818) and for M6G were 0.643 (0.39–0.957) and 0.423 (0.267–0.579). Conclusion This study demonstrates that the CYP2D6*10 allele plays an important role in the pharmacokinetics of the O-demethylated metabolites of codeine after oral administration.